MODERN APPROACHES TO THE MANAGEMENT OF THE QUALITY OF EDUCATIONAL SERVICES IN HIGHER EDUCATIONAL INSTITUTIONS AND THE SYSTEM OF USE OF PEDAGOGICAL TECHNOLOGIES - Yunusovna, Norova Kamola; Gafurova, Shakhloxon Karimovna (International Journal of Psychosocial Rehabilitation, 2020)
Arrangement of management activity in edicating institution is the most actual to education and training quality growth. There is provided theoretical visions of researchers and payed attention to effective management factors in the article. As well there are disclosed notions for efficiency of management activity.